POTENSI PENYERAPAN TENAGA KERJA MELALUI PENGUATAN SEKTOR PERTANIAN DI SUMATERA UTARA - JIMMY SAPUTRA SEBAYANG (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2020)
The economic crisis triggered by the COVID-19 epidemic has affected the labor situation in North Sumatra. Temporary or permanent business closings, also employee reductions to cut production costs have led to an increase in layoffs and the unemployment rate. To overcome the large increase in unemployment, it is necessary to encourage the absorption of labor. One of the most potential sectors is Agriculture. By using a descriptive method with a qualitative approach and a Location Quotient (LQ) analysis method, it is concluded that the agricultural sector has the potential to be developed as an economic driver for employment in North Sumatra Province. Strengthening and developing the agricultural sector in North Sumatra is considered to be able to attract a large number of workers and reduce the spike in unemployment during the COVID-19.